FINANCIAL PERFORMANCE AND VALUATION ASSESSMENT OF PT PERUSAHAAN GAS NEGARA IN COMPARISON TO PETRONAS GAS BERHAD - Blandina Pardede, Felicia
Indonesia is ranked the 12th world’s largest natural gas producer with production capacity of 2,371.58 BSCF in 2019. Domestic consumption has grown tremendously over the last 10 years. Indonesia gas domestic consumption increased from only 47 percent back in 2009 to 64 percent in 2019. PT Perusahaan Gas Negara (PGN) operates the gas transmission and distribution system and infrastructure in Indonesia, serving 92% of the domestic market. On the other hand, Petronas Gas Berhad (PGB) is the backbone of Malaysia’s gas transportation system. Both companies are public company subsidiary of its respective country’s National Oil Company, namely Pertamina and Petronas. This final project conducts financial ratio analysis based on companies’ financial report year 2015-2019 to evaluate the historical performance. Meanwhile, valuation assessment was carried out on PGN to determine the company's fair value in relation to the COVID-19 pandemic which affects the company's business. Financial ratio analysis conducted in this project included profitability ratio, liquidity ratio, activity ratio, solvency ratio, market value ratio, DuPont analysis and validation using the decree of Ministry of SOE No. KEP-100/MBU/2002 tanggal 04 Juni 2002. Furthermore, PGN’s company intrinsic value was analyzed using the free cash flow to the firm (FCFF) method. From the study, it is concluded that both PGN and PGB has good financial performance and the intrinsic value of PGN stock price is Rp 1,449 per share while the current stock price is Rp 1,805 per share (Dec 18, 2020), thus the stock price is overvalued.